2022
DOI: 10.4103/ijmr.ijmr_70_22
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID multisystem inflammatory syndrome in adults: a study from a tertiary care hospital in south India

Abstract: Background & objectives: There are limited data from India on the post-COVID multisystem inflammatory syndrome in adults (MIS-A). The objective of the present study was to evaluate the clinical profile of patients with MIS-A admitted to a tertiary care centre in southern India. Methods: This single-centre retrospective study was conducted from November 2020 to July 2021, and included patients aged >18 yr admitted to the hospital as per the inclusion and exclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Although the children counterpart of MIS‐A typically occurs within 2–6 weeks post COVID‐19 infection, 6–8 MIS‐A may occur up to 4 months after‐COVID‐19 infection as seen in our patient. Existing literature suggests that early treatment with IVIG, high‐dose prednisolone 8 and interleukin‐6 blockade results in rapid improvement in clinical condition and inflammatory markers 9 . The use of aspirin in MIS‐A is reported in some case reports 10,11 .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Although the children counterpart of MIS‐A typically occurs within 2–6 weeks post COVID‐19 infection, 6–8 MIS‐A may occur up to 4 months after‐COVID‐19 infection as seen in our patient. Existing literature suggests that early treatment with IVIG, high‐dose prednisolone 8 and interleukin‐6 blockade results in rapid improvement in clinical condition and inflammatory markers 9 . The use of aspirin in MIS‐A is reported in some case reports 10,11 .…”
Section: Discussionmentioning
confidence: 53%
“…MIS‐A, like its paediatric counterpart (MIS‐C), can present very similarly to KD, with florid mucocutaneous rashes and sometimes with cardiogenic shock requiring inotropic support 3–5 . Although the children counterpart of MIS‐A typically occurs within 2–6 weeks post COVID‐19 infection, 6–8 MIS‐A may occur up to 4 months after‐COVID‐19 infection as seen in our patient. Existing literature suggests that early treatment with IVIG, high‐dose prednisolone 8 and interleukin‐6 blockade results in rapid improvement in clinical condition and inflammatory markers 9 .…”
Section: Discussionmentioning
confidence: 56%
“…MIS-A predominantly affects males between 30 and 50 years of age. The most common presenting symptoms are fever and gastrointestinal symptoms, as in our patient [ 8 ]. Cardiac involvement is frequent but is not universally present, as evidenced by a recent systematic review and as observed in our case, in which there was no cardiac involvement [ 4 ].…”
Section: Discussionmentioning
confidence: 90%
“…For example, a recently published observational study found increased PCT in patients with postCOVID-19 (coronavirus disease 2019) multisystem inflammatory syndrome. [ 11 ] Yu et al[ 12 ] found that the main cause was rhabdomyolysis in a patient who was followed up with the assumption of sepsis and whose PCT values increased considerably. PCT was found to be high in the acute period of Kawasaki disease in children, particularly in those who were resistant to intravenous immunoglobulin therapy.…”
mentioning
confidence: 99%